Biomechanical behavior of mandibles reconstructed with fibular grafts at different vertical positions using finite element method. Issue 2 (February 2019) - Cheng, Kang-jie; Liu, Yun-feng; Wang, Joanne H.; Jun, Janice C.; Jiang, Xian-feng; Wang, Russell; Baur, Dale A.
Summary: Background: For large mandibular defects, surgical reconstruction using microvascular fibular grafts has advantages over other alternatives in terms of blood supply and good quality of grafted bone. However, the fibular segment is usually lower in height than that of the original mandible, meaning that the vertical positioning of the fibular graft is variable, with different biomechanical consequences on the reconstructed mandible. Objectives: To use finite element method (FEM) to evaluate stress distribution and displacement of a reconstructed mandible versus an intact mandible under occlusal loads. Methods: A three-dimensional intact edentulous mandibular bone (Model I) and a reconstructed mandible bone with fibular graft were created from CBCT images. Calculation models were generated with fibular bone graft extracted from the reconstructed mandible of identical length placed into a mimicked defect area on the right-hand side of the mandible at three different vertical positions: superior (Model II), intermediate (Model III), and inferior (Model IV). Forces were applied at lower left first molar region and lower left central incisor area. Von Mises stresses and mandibular displacement were calculated as outcome measurements during loadings. Results: Maximum stress and strain within the reconstructed mandible were identified at the posterior border of the graft and the contralateral condyle. Maximum displacement occurred near the interface of fibular graft and anterior segment of the mandible. Stress distribution in the graft under functional loads is much higher than that in the residual mandibular segments from Models II to IV. The combined average maximum stress from anterior and posterior loads is 10.66 times higher in the mandible with inferiorly positioned graft (Model IV), 8.72 times for superior graft (Model II), and 3.68 times for intermediate graft (Model III) than that in the control group (Model I). The worst displacement result during functional loadings was in the group with fibular graft located at the inferior border of the mandible. Conclusions: The position of fibular graft placed in the surgical resection site has significant effects on the mechanical behavior of the reconstructed mandible. The fibular graft aligned with the inferior border of the mandible, the most common site designated location by clinicians, has the worst effects on the stress distribution and displacement to the mandibular under functional loads. The fibular graft placed at the intermediate location has the best biomechanics and provides favorable condition for subsequent prosthetic reconstruction.